Role of general practitioners in managing common mental-neurological and substance use (MNS) disorders in rural Nepal: a qualitative study from provincial hospital - Dangal, Binod; Pandya, Apurva Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Mental health disorders are the leading cause of morbidity worldwide and the prevalence ranges from 4.3% (China) to 26.4% (United States) annually. Depression and anxiety are the leading causes of disability. Major strategies of mental health care in remote Nepal have limited district level care. This study examines General practitioner's role in managing common mental neurological and substance use (MNS) disorders in remote Nepal with collaborative care model. Method: This study employs qualitative approach at Pashupati Chaulagain Memorial Hospital. With purposive sampling technique, in-depth semi-structured interviews with 40 patients (N=40), 3 GPs (N=3) and 1 mental health expert (N=1) done. A 10 minutes long questionnaire comprising 15 items were asked and 30-minute interview was taken. Thematic analysis was carried out. Result: Patients reported positive experiences of the model. Among 40 patients, mainly 50% comprised of depression, 25% of anxiety disorder, and 15% of Psychosis and 10% comprised of alcohol use disorder. Successful treatment, patient satisfaction, regular services, strong supply chain and counseling by psychosocial counselor were the main rewards in the model. The challenges identified were stigma, poverty, and poor infrastructure development, need of guidance and supervision of the program. Conclusion: General practitioners play an important role in the provision of common mental health disorders in the remote setting of Nepal. A collaborative care model led by GPs have shown promising evidence in treating mental health patients effectively. Developing communication with GP-mental health professionals, organizing training programs for GPs, policy advocacy, motivational benefits and psychotropic medicine management can improve overall mental health care.